Analisis Kepribadian Atlet Porprov Tahun 2023 Di Kabupaten Banyumas - Norma Dyah Pratiwi; Heny Setyawati (Indonesian Journal for Physical Education and Sport, 2024)
This research aims to analyze the personality of Banyumas Regency PORPROV athletes who compete in PORPROV IX Central Java 2023. The method used in this research is a survey using a quantitative approach. The sample in this study consisted of 104 athletes, with details of 67 male athletes and 37 female athletes from 38 sports. Data collection techniques and instruments were carried out using the Sport Personality Questionnaire (SPQ-20) adopted from (Cameron, 2012) which was distributed online with a total of 168 questions. The data analysis technique uses quantitative percentages. The research results showed that overall Banyumas Regency PORPROV athletes had a high level of personality with an average score of 3.69 with details of 1 athlete in the very high category, 72 athletes in the high category, 30 athletes in the average category, and 1 athlete in the low category. The dominant personality indicators are achievement, adaptability, competitiveness, conscientiousness, visualization, goal setting, self-efficacy, flow, stress management, emotion, self-talk, self-awareness, ethics, and impression management. Personality indicators that need to be improved are intuition, managing pressure, fear of failure control, empathy, relationships, aggressiveness, power